Integrasi Hadis dalam Tafsir Al-Tahrir Wa Al-Tanwir Karya Ibnu ‘Asyur - Mawaliya Mawaliya; Uswatun Hasanah (Indo Publishing, 2025)
This research is to determine the integration of Hadith in Tafsir Al-Tahrir Wa Al-Tanwir by Ibnu 'Asyur. Ibn 'Asyur emphasized that the interpretation of the Qur'an must be based on two main pillars: First, the authority of the Prophet's hadith as explanation (al-bayan). Second, linguistic-balaghah analysis as a fundamental method. Muhammad Ibn 'Asyur's approach in writing his tafsir can be concluded as an analytical method (tahlili) which includes one methodology, namely the bil-lughah method or entering the tahlili method. Muhammad Tahir Ibn 'Asyur divides maqasid al-syari'ah into two, first, maqasid al-tasyri' al-ammah are the hidden meanings and wisdom in all or the majority of laws. Second, maqasid al-khasah are the methods desired by the Shari' to realize human benefits.